Ordered Iron‐ and Nitrogen‐Doped Carbon Framework as a Carbon Monoxide‐Tolerant Alkaline Anion‐Exchange Membrane Fuel Cell Catalyst. Issue 6 (2nd May 2018) - Chen, Lei; Xing, Yijing; Cai, Shichang; Wang, Rui; Li, Shang; Li, Junsheng; Guo, Wei; Tang, Haolin
Abstract: In this work, we have successfully developed a series of ordered Fe‐ and N‐doped carbon (Fe‐N‐C) catalysts for alkaline anion‐exchange membrane fuel cells (AEMFCs) using ordered SiO2 nanospheres as a scaffold template. Compared to the previous work, the SiO2 nanosphere templates used in this work are more well‐ordered and size‐controlled, which increases the surface area of the Fe‐N‐C framework material. We observed that the 30 nm@Fe‐N‐C sample exhibits orderly arranged mesopores, interconnected conductive networks, and large surface area (1192 m 2 g −1 ). Moreover, the 30 nm@Fe‐N‐C sample shows significantly enhanced oxygen reduction reaction (ORR) activity compared to commercial Pt/C. A more‐positive half‐wave potential of 0.84 V (vs. reversible hydrogen electrode, RHE) and remarkably stable limiting current of ≈6.1 mA cm −2 is demonstrated by a three‐electrode configuration rotating disk electrode (RDE) system in 0.1 m KOH solution. An AEMFC based on the 30 nm@Fe‐N‐C sample showed a maximum power density of 100 mW m −2 at a high current density of 230 mA cm −2 . In addition, we found the AEMFC based on 30 nm@Fe‐N‐C catalyst could steadily operate for more than 60 h with only 4.65 % performance degradation under constant voltage conditions (0.6 V). More interestingly, this catalyst shows an excellent tolerance for CO as well as remarkably long‐term stability with more than 89.9 % retention of its initial activity after 41.6 min operation, which is obviously superior to the commercial Pt/C catalyst (59 % initial activity retention). Abstract : Preaching CO tolerance : A series of ordered Fe‐ and N‐doped carbon (Fe‐N‐C) catalysts are fabricated in this work for alkaline anion‐exchange membrane fuel cells (AEMFCs) by using ordered SiO2 nanospheres as a scaffold template. Compared to previous work, the SiO2 nanosphere templates used in this work are more well‐ordered and size‐controlled, which increases the surface area of the Fe‐N‐C framework material.